Literary Crisis in the Age of Film and Television: Starting from Postcolonial - Li, Laijin (International Journal of Social Sciences and Public Administration, 2024)
From the macro perspective of post-colonial, this paper explores the modern crisis of traditional literature in the era of film and television in which technology carnival and traffic are Paramount, and points out that literature will not die out in the era of technology, but will be accompanied by mass media towards consumerization and popularization.